Instructional leadership in Greek and English outstanding schools - Kaparou, Maria; Bush, Tony (Emerald, 2016)
Purpose – The purpose of this paper is to examine instructional leadership (IL) in outstanding secondary schools within a centralised (Greece) and a partially decentralised (England) education context.